Assessing Differential Knowledge Level Apropos Improved Sugarcane Cultivation Practices in Madhya Pradesh - Sandeep Chouhan , S.R.K. Singh , A.K. Pande U.S. Gautam, Shrankhla Mishra, (Indian Journal of Extension Education, 2022)
Knowledge is the essential component for enhancing the production and income of farmers. This research study was conducted in Burhanpur districts of Madhya Pradesh during 2011-12, with the sample size of 120 respondents. Theex post facto research design was used for the study.The findings revealed that, around 76.66 per cent respondents possessed mediumknowledge level.Anegligible percentage of the respondents i.e. 15.84 per cent and 7.50 per cent had lowand high knowledge level, respectively. Themaximumproportions of the respondents (52.5%)were havingmiddle level of annual income ( 2.01 -5.00 lakh) followed by 34.16 per cent low income (< 2 lakh) and 13.34 per cent high annual income (> 5.01 lakh).The results indicated a need for greater extension effort to provide know-how of the improved sugarcane production technologies to the respondents. The role of extension agents are to remove the barrier by providing information and insight into the problem for enhancing the sugarcane productivity vis-à-vis income of the sugarcane growers .